UNIVERSAL MODEL FOR ORGANIZATIONAL STRUCTURE IN THE POSTGRADE UNITS OF UNMSM - Valdivia Ramos, Román Arturo (2011)
For the first time in an academic level, is proposing a universal model of organizational structure, in this case, Units Graduate UNMSM (and could not be otherwise, had to be the dean of American University) , which of course can be used or implemented not only in the UPG of our university, but in the Faculties, CEUPS, Research Institutes and all organic unity is academic or administrative. So what we are calling: Universal. State or public universities, including San Marcos University, can not escape the traditional, routine, to which it is used or the style and usage and style to plot structures, has remained unmovable, unchangeable, unchanged from decades ago. Peter F. Drucker said the only constant is change. But sometimes we forget. We got carried away by the routine. But our university has vision, has desires, is teleological, ie visa to distant future and, therefore, is constantly innovative, ahead of other universities (as it should be), then, raises new situations, it listens come or to come. And in that way, we are: anticipating the future. Of course, that the organizational structure we will use the Model AFNOR, is nothing new to European or American academia, but if it is for us, so no one until now has some college designed and implemented under we are the first.